How commercial banks adjust capital ratios: Empirical evidence from the USA?‎ - Faisal Abbas; Shoaib Ali; Imran Yousaf; Sohail Rizwan (Cogent Business & Management, 2020)
This study examines the speed of adjustment of the leverage and regulatory capital ratios between 2002 and 2018 for large commercial banks of the USA. The study applies a two-step system GMM technique to obtain the speed of adjustment. The results prove that higher-quality capital requires greater time to restore equilibrium after an economic shock. The results also show that large commercial banks adjust their regulatory ratios faster than leverage ratios. Furthermore, the speed of adjustment is heterogeneous for cross-sections. The speed of adjustment for well-capitalized banks is higher than adequately and undercapitalized commercial banks. The speed of adjustment for highly liquid is higher than low liquid banks. This study also finds the banks quickly adjust their capital before the crisis period. The heterogeneous results have implications for regulators, policymakers, and bank managers for better decision making.
Keywords: G20; G21; G28; G32; 650; leverage ratio; regulatory ratios; capital buffer ratio; speed of adjustment